2017
DOI: 10.5455/apd.258477
|View full text |Cite
|
Sign up to set email alerts
|

Mental assessment of girls consulting for early marriage and identifying risk factors

Abstract: %18.8'inde (n=15) DEHB, %5'inde (n=4) davranım bozukluğu, %3.8'inde (s=3) anksiyete bozukluğu, %2.5'inde (s=2) major depresif bozukluk, %1.3'ünde (s=1) uyum bozukluğu, %6.3'ünde (s=5) zeka geriliği, %20'sinde (s=16)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
2
2
0
2
Order By: Relevance
“…Mean age at first child birth is 15years. Also, this comes in agreement with a study done in Turkey for mental assessment of girls consulting for early marriage and identifying risk factors (13) who found in the studied sample that their age ranged between 16-17years old . One third of mothers can't read and write and the majority of them weren't working while the majority of fathers had primary education and working.…”
Section: Discussionsupporting
confidence: 92%
“…Mean age at first child birth is 15years. Also, this comes in agreement with a study done in Turkey for mental assessment of girls consulting for early marriage and identifying risk factors (13) who found in the studied sample that their age ranged between 16-17years old . One third of mothers can't read and write and the majority of them weren't working while the majority of fathers had primary education and working.…”
Section: Discussionsupporting
confidence: 92%
“…As regard to student's perception toward regarding adverse health consequences of early marriage the present study revealed that the minority of students had positive perception in preprogram implementation, while changed to majority of them post program with highly statistically significant differences pre/post program implementation. The previous results complies with the study in Pakistan about Knowledge and attitude towards child marriage practice among women married as children-a qualitative study in urban of slums of Lahore Nasiroglu & Semerci [20] who founded that the majority of the participants were unaware of the negative health outcomes of child marriages. There should be health awareness programs conducted for the girls as well as their parent to overcome the problems caused due to early marriages and to improve their quality of lives.…”
Section: Discussionsupporting
confidence: 87%
“…It has also been reported in various studies that there is an increased prevalence of psychiatric disorders in adolescents who married before the age of 18 in Turkey. These rates vary between 24.7% and 45.8% (12,15,16,28). The fact that our study is the study with the largest sample size in country so far is a situation that might be taken into account when interpreting these data, as the reason for this difference may be the number of samples.…”
Section: Discussionmentioning
confidence: 84%